2021
DOI: 10.1007/s11738-021-03289-z
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic responses of durum wheat to chemical/microbiological fertilization management under salt and drought stresses

Abstract: The current research was carried out to evaluate the stress tolerance potential of durum wheat plants, in response to the inoculation of native plant growth-promoting bacteria (PGPB), through assessing PSII photochemistry and photosynthetic traits, as well as grain yield and plant height, and to investigate the possibility of using PGPB as a sustainable alternative or in combination with traditional fertilization plans. A greenhouse experiment included chemical/microbiological fertilization and stress (salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 54 publications
8
27
0
Order By: Relevance
“…As reported earlier (Yaghoubi Khanghahi et al, 2021a), fertilisation treatments increased grain yield under both non‐stress and stress conditions. The grain yield reached the highest value in non‐stress, drought, and salinity when treated with respectively BC + ½CF (1.05 g plant −1 ), BC (0.46 g plant −1 ), and BC (0.61 g plant −1 ).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…As reported earlier (Yaghoubi Khanghahi et al, 2021a), fertilisation treatments increased grain yield under both non‐stress and stress conditions. The grain yield reached the highest value in non‐stress, drought, and salinity when treated with respectively BC + ½CF (1.05 g plant −1 ), BC (0.46 g plant −1 ), and BC (0.61 g plant −1 ).…”
Section: Resultssupporting
confidence: 82%
“…As fully described by Yaghoubi Khanghahi et al (2021a), durum wheat seeds (var. Furio Camillo) and the clay loam soil were collected for the greenhouse experiment from the same durum wheat fields where the PGPBs were isolated.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, putrescine alleviated the salt-induced damages and increased the level of glutathione and carotenoids in Brassica juncea [29]. Mohammad et al, [42] had reported increased carotenoid content in durum wheat plants when inoculated with plant growthpromoting bacteria (PGPB) under mild salt stress conditions and protect photosynthetic reaction centres.…”
Section: Biochemical Response Of Non-enzymatic Antioxidant System During Salt Stress and Spermine Treatmentmentioning
confidence: 99%
“…Groups of rhizosphere microorganisms and their interactions are the subject of research aimed at determining their influence on the growth, yield, and protection of plants [ 6 , 7 , 8 ]. These organisms colonize the roots of plants and induce growth and immune processes in them, which can contribute to the neutralization or minimization of the impact of stresses caused by, for example, water deficiency [ 9 , 10 , 11 , 12 ], high temperature [ 13 , 14 ], low temperature [ 15 ], salinity [ 16 , 17 ], soil contamination with heavy metals [ 18 , 19 ], or biotic factors (pathogens) [ 20 , 21 ]. Among free-living bacteria are Plant Growth Promoting Rhizobacteria (PGPR), which have been utilized for improving water and nutrient uptake and abiotic and biotic stress tolerance [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%